Social Media Campaign Strategies: A Case Study of Political Issue Framing by 2024 Presidential Candidates in Ghana - Alexander Tawiah (Journalism and Media, 2025)
Despite extensive scholarship on social media political party strategies or intra-party-political campaigns across digital platforms, it remains relatively unexplored how individual presidential candidates adopt social media to frame their messages on key political issues for voter engagement, especially in the West Africa region. To fill this gap, this study examines how the two major presidential candidates in Ghana, John Mahama of the National Democratic Congress (NDC) and Mahamudu Bawumia of the New Patriotic Party (NPP), use social media platforms to frame key political issues during the 2024 election campaign. Using framing theory and digital multimodal discourse analysis as the conceptual and methodological frameworks, the study examines content on X (formerly Twitter), Facebook, and Instagram, with a focus on issues related to the economy and education, while also assessing how platform-specific affordances shape the presentation and visibility of these frames. The findings of the study reveal three core dynamics in the framing strategies of both candidates: (1) contrasting economic narratives (‘Resetting Ghana’ vs. ‘It Is Possible’), (2) competing visions of education (reform vs. continuity), and (3) platform-specific engagement patterns. These findings offer insight into how political actors leverage digital affordances beyond simple messaging tools into structured framing mechanisms and strategically construct narratives to shape public discourse and influence voter engagement.